2003
DOI: 10.1016/s0736-0266(02)00093-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroCT evaluation of normal and osteoarthritic bone structure in human knee specimens

Abstract: Although trabecular bone structure has been evaluated, variation with knee compartment and depth from joint surface is not completely understood. Cadaver knees were evaluated with microcomputed tomography analysis for these variations. Objective differences were compared between: medial vs. lateral compartments; femoral vs. tibial bone; and normal vs. arthritic knees. Depth dependent changes in the parameters were observed for the first 6 mm of the cores in normal knees: BV/TV, Tb.N and Conn.D gradually decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
93
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 33 publications
11
93
0
2
Order By: Relevance
“…Micro-CT analysis was used to evaluate morphologic bone changes that are consistent with OA. A decrease in trabecular bone thickness and a loss of bone density has been shown in OA (35). The C57BL/6 mice in this study had a decrease in bone density in the fractured limb compared with the control limb at 4 and 8 weeks postfracture, which is consistent with OA changes previously reported clinically (35,36) and in animal models (7,37,38).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Micro-CT analysis was used to evaluate morphologic bone changes that are consistent with OA. A decrease in trabecular bone thickness and a loss of bone density has been shown in OA (35). The C57BL/6 mice in this study had a decrease in bone density in the fractured limb compared with the control limb at 4 and 8 weeks postfracture, which is consistent with OA changes previously reported clinically (35,36) and in animal models (7,37,38).…”
Section: Discussionsupporting
confidence: 91%
“…A decrease in trabecular bone thickness and a loss of bone density has been shown in OA (35). The C57BL/6 mice in this study had a decrease in bone density in the fractured limb compared with the control limb at 4 and 8 weeks postfracture, which is consistent with OA changes previously reported clinically (35,36) and in animal models (7,37,38). However, the MRL/MpJ mice did not show a decrease in bone density in the fractured limb as compared with the control limb in the metaphyseal region of the tibia.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, histomorphometry cannot accomplish precise quantitative analysis of such parameters as TMD and BMD. Micro-CT makes it an ideal technique to investigate spatial properties at the bone-screw interface and enables three-dimensional quantitative analysis [24]. Studies indicated that micro-CT at a voxel size of 24 lm enabled the detection of bone changes earlier than histomorphometry in a model of osteoporosis in rats killed at different time points [2,12].…”
Section: Discussionmentioning
confidence: 99%
“…7,9,29 Furthermore, in the indirect approach most microstructural parameters are derived from very few basic parameters, so that the microstructural parameters have a strong interrelation by definition. To account for the dependence of the trabecular microstructural parameters on the depth position relative to the bone surface 11,27,28 the bone samples were divided into two volumes of interest (VOIs) of different depth positions. The first VOI starts directly beneath the cortical layer and ends 5 mm beneath the cortical layer (subcortical region) and the second VOI starts 5 mm beneath the cortical layer and ends 10 mm beneath the cortical layer (inner region).…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] From comparative studies a wide range of microstructural parameters is reported, depending on donor age, bone type, and bone region.…”
mentioning
confidence: 99%